Numerično modeliranje notranjih zvokov v železniških vozilih - Bazaras, Jonas (Strojniški vestnik, 2007)
The paper presents an analysis of the sound in railway rolling stock. The speeds of trains tend to increase as railway rolling stock improves technically and becomes more sophisticated: however, the sound generated is intensified too. Noise is one of the harmful consequences of transport. As thesound level in domestic surroundings is one of the most important human-comfort indices, increasing attention is being devoted to an investigation of sound processes. The sound generated by transport vehicles, its distribution, and its variation in internal transport-vehicle spaces, and various sound sources in railway transport are considered in the paper. Engineering, organizational and administrative sound-reducing measures are discussed. The harmful effects of sound on human health are discussed as well. Two types of Russian production locomotives - the M62 and the TEP60 - were selected for this research. Using ANSYS/Multiphysic software the acousticsound of the different power units in the engine sector was simulated.The results of the sound calculations were compared with the acceptable levels.
Keywords: železniška vozila; zvok; hrup; numerično modeliranje; dušenje hrupa